The Effect of Supplementary Feeding with Different Pollens in Autumn on Colony Development under Natural Environment and In Vitro Lifespan of Honey Bees - Erkan Topal; Rodica Mărgăoan; Veysel Bay; Çiğdem Takma; Banu Yücel; Devrim Oskay; Gamze Düz; Sezer Acar; Mustafa Kösoğlu (Insects, 2022)
Honey bees need pollen and nectar sources to survive in nature. Particularly, having young bees in colonies is vital before wintering, and proper feeding is necessary to achieve this. In the present study, the effect of feeding with pollen sources of different protein content on colony performance, wintering ability and in-vitro longevity of colonies that weakened after feeding with pine honey in autumn, or that needed to enter the winter period, was investigated. The experiment was carried out in 48 colonies divided into six groups as follows: control, syrup, mixed pollen, Cistus creticus pollen (Pink rock-rose), Papaver somniferum pollen (Opium poppy), and commercial bee cake groups. In particular, the P. somniferum pollen group was different (p < 0.01) from the other experiment groups with the number of bee frames (3.44), the area with brood (1184.14 cm2) and the wintering ability of 92.19%. The effect of nutritional differences on survival was found to be statistically significant in vitro and this supports the colony results in the natural environment (p < 0.001). The P. somniferum group has the longest longevity with 23 days. Pollen preferences of honey bees were P. somniferum, C. creticus, and mixed pollen, respectively.